Technical Feasibility of a Combined Noncontrast Magnetic Resonance Protocol for Preoperative Transcatheter Aortic Valve Replacement Evaluation. Issue 1 (January 2018) - Cannaò, Paola M.; Muscogiuri, Giuseppe; Schoepf, U. Joseph; De Cecco, Carlo N.; Suranyi, Pal; Lesslie, Virginia W.; Piccini, Davide; Giri, Shivraman; Varga-Szemes, Akos
Abstract : Purpose: The aim of this study was to prospectively evaluate the technical feasibility of a noncontrast magnetic resonance angiography (MRA) protocol using investigational prototype self-navigated 3D (SN3D) radial whole-heart and quiescent-interval single-shot (QISS) pulse sequences regarding their potential in planning transcatheter aortic valve replacement (TAVR). Materials and Methods: Five patients (76±7 y) with severe aortic valve stenosis and prior computed tomographic angiography (CTA) for TAVR planning and 10 healthy volunteers (28±6 y) underwent noncontrast MRA on a 1.5 T system. A SN3D whole-heart acquisition was used to assess the aortic root anatomy. Evaluation of the aortoiliac access route was performed with both SN3D and QISS. Measurements were compared among SN3D, QISS, and CTA using a paired t test or 1-way analysis of variance. Image quality ratings and contrast-to-noise ratios (CNR) were analyzed using Mann-Whitney U tests. Interobserver agreement was evaluated using Cohen's κ. Results: The combined SN3D and QISS protocol provided a 10.1±1.6-minute acquisition time. TAVR-relevant evaluation was technically feasible in healthy volunteers. All measurements showed good agreement with CTA in patients (all P >0.098). SN3D and QISS produced similar image quality both in volunteers and in patients (all P >0.122). There was no difference in qualitative ratings between MRA and CTA (all P >0.119). Interobserver agreement was good for MRA (κ=0.71 to 0.76) and excellent for CTA (κ=0.82 to 0.84). Thoracic SN3D provided a similar CNR compared with CTA ( P =0.117). CTA yielded higher CNR in the abdominopelvic region compared with QISS ( P =0.006). Conclusions: A noncontrast MRA protocol combining SN3D and QISS acquisitions for the assessment of cardiac and vascular access route anatomy has technical feasibility for TAVR planning.